Enterprise restructuring in Belarus - Marina Bakanova; Saul Estrin; Igor Pelipas; Sergei Pukovich (Institute for the Study of Labor (IZA), 2006)
We explore the impact of privatization and the entry of new firms on enterprise performance in Belarus, a transition economy in which reform and market-orientated institutional development has been limited. We hypothesize that private ownership will enhance company performance, measured in a variety of ways including profitability and capacity to export to the West, and that newly created firms will perform better than state-owned ones. Our work is based on a large enterprise level survey which includes state-owned firms, privatized companies and newly created enterprises. The data refute both hypotheses. We conclude that this is probably because the institutional environment has not evolved sufficiently from the socialist era to permit free competition and effective governance by new owners.
Keywords: P2; P31; L1; 330; enterprise restructuring; privatization; transition; Belarus; Privatisierung; Markteintritt; Unternehmensentwicklung; Weißrussland